Benefits and drawbacks of open partial horizontal laryngectomies, Part A: Early‐ to intermediate‐stage glottic carcinoma. (16th June 2015) - Succo, Giovanni; Crosetti, Erika; Bertolin, Andy; Lucioni, Marco; Caracciolo, Alessandra; Panetta, Valentina; Sprio, Andrea Elio; Berta, Giovanni Nicolao; Rizzotto, Giuseppe
ABSTRACT: Background: Laryngeal squamous cell carcinoma (SCC) accounts for 1.9% of cancers worldwide. Most of these are diagnosed in the early stages (T1–T2, and N0). For these, a larynx preserving/conserving option is preferable. Beyond transoral laser microsurgery (TLM), open partial horizontal laryngectomy is a function‐sparing surgical technique used to treat laryngeal SCC. Methods: We retrospectively analyzed the clinical outcomes of 216 patients who underwent open partial horizontal laryngectomy for glottic cT2 laryngeal cancer. Results: Five‐year overall survival (OS), disease‐specific survival (DFS), locoregional control, local control, laryngeal function preservation, and laryngectomy‐free survival rates were 93.1%, 98.0%, 97.1%, 97.5%, 97.8%, and 98.5%, respectively. Disease controls were significantly affected by previous treatment and type of surgery used. Conclusion: Although TLM for cT2 laryngeal cancer with unimpaired vocal cord mobility still represents a sound option, open partial horizontal laryngectomy offers higher local control and laryngeal preservation rates for selected patients with impaired mobility of vocal cords combined with involvement of the paraglottic space. © 2015 Wiley Periodicals, Inc. Head Neck 38 : E333–E340, 2016